Hydrothermal treatment with VO2(B) nanobelts for synthesis of VO2(A) and W doped VO2(M) nanobelts. (April 2015) - Zhang, Y.; Tan, X.; Huang, C.; Meng, C.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, the conversion of VO2(B) nanobelts under the hydrothermal condition in the absence/presence of dopant was studied. The synthetic conditions, such as the reaction temperature, reaction time, quantity of the dopants and kinds of dopants, were briefly discussed to prepare VO2(A) and W doped VO2(M) solid solution. It was found that the dopant played a crucial role in controlling VO2 polymorph, and the results showed that VO2(A) was obtained in the absence of dopant, whereas W doped VO2(M) was obtained in the presence of tungstenic acid. The transformation mechanism from VO2(B) to VO2(A) and W doped VO2(M) was discussed in detail. The phase transition temperature (Tc) of VO2(A) and W doped VO2(M) was evaluated by differential scanning calorimetry. It is found that doped atoms can be successfully doped into the crystal lattice of VO2(M) matrix, and the Tc of W doped VO2(M) can be reduced by W doping. The optical switching properties were studied by the variable temperature infrared spectra, and it was found that the as obtained VO2(A) and W doped VO2(M) had outstanding thermochromic characters and optical switching properties.